Mr Midshipman Hornblower - Forester, C. S. (Little Brown, 2000)
'Hornblower fired. There was a small cloud of smoke, but no bang. This is death, he thought. My pistol was the unloaded one.' But Horatio Hornblower does not die. He survives the duel with Simpson, learns to overcome his seasickness, and goes on to risk his life many times over. It is 1793, Britain is at war with France, and life on a sailing ship of war is hard and dangerous. But the hardest battles are fought by Hornblower within himself